Evolutionary shape optimization in fracture problems - Beluch, Witold (Computer Assisted Methods in Engineering and Science, 2022)
The aim to the paper is to optimize 2-dimensional elastic structures subjected to cyclic load. The loading can result in crack forming, so the aim of the optimization is to reduce the possibility of crack growth. The number of loading cycles necessary to crack growth is maximized. To solve the optimization task the evolutionary algorithm is used. The boundary element method is applied to solve the crack problem. In order to reduce the number of design variables the parametrical NURSB curves are used to model the geometry of parts of the structural element boundary.